Individual differences and personality - Cooper, Colin (Oxon Routledge, 2021)
"This book includes comprehensive coverage of both personality theories and the methodological issues associated with personality and psychometric testing, as well as individual differences and intelligence. The book examines topics such as personality traits and types, measurement of abilities, and applications of personality theory. The new edition includes a new chapter on trait theories and a second chapter on applications. There is increased coverage of the dark triad, creativity, and counselling psychology. With self-assessment questions, further reading and a companion website, this is the ideal resource for anyone taking modules on personality and individual differences"--
Includes bibliographical references and index.
Keywords: Personality; Individual differences; Individuality; Psychology